2016
DOI: 10.1126/science.aaf8156
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and spread of a human-transmissible multidrug-resistant nontuberculous mycobacterium

Abstract: Lung infections with Mycobacterium abscessus, a species of multidrug resistant nontuberculous mycobacteria, are emerging as an important global threat to individuals with cystic fibrosis (CF) where they accelerate inflammatory lung damage leading to increased morbidity and mortality. Previously, M. abscessus was thought to be independently acquired by susceptible individuals from the environment. However, using whole genome analysis of a global collection of clinical isolates, we show that the majority of M. a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
568
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 493 publications
(603 citation statements)
references
References 53 publications
30
568
4
1
Order By: Relevance
“…massiliense (M) and M. abscessus subsp. bolletii (B) as independent species.This paper is in clear contradiction with our own recent work [2] published in 2016.The claim of the authors (1st page) that postgenomic analysis 'unambiguously supports the reinstatement of species' seems to us at least highly questionable; in none of the studies they cited in their paper [3][4][5][6][7][8], with the exception of one study [9] done in collaboration with the same authors, is the status of subspecies questioned.A major argument supporting the suggestion of Adekambi et al was published by him in 2008 [10]. The major conclusions of this work were that 1) an rpoB gene similarity 97.7 % correlates with a DNA-DNA Hybridization (DDH) <70 %; and 2) the DDH may be inferred by the formula: 5.98(rpoB similarity)-2516.1.…”
contrasting
confidence: 54%
See 1 more Smart Citation
“…massiliense (M) and M. abscessus subsp. bolletii (B) as independent species.This paper is in clear contradiction with our own recent work [2] published in 2016.The claim of the authors (1st page) that postgenomic analysis 'unambiguously supports the reinstatement of species' seems to us at least highly questionable; in none of the studies they cited in their paper [3][4][5][6][7][8], with the exception of one study [9] done in collaboration with the same authors, is the status of subspecies questioned.A major argument supporting the suggestion of Adekambi et al was published by him in 2008 [10]. The major conclusions of this work were that 1) an rpoB gene similarity 97.7 % correlates with a DNA-DNA Hybridization (DDH) <70 %; and 2) the DDH may be inferred by the formula: 5.98(rpoB similarity)-2516.1.…”
contrasting
confidence: 54%
“…The claim of the authors (1st page) that postgenomic analysis 'unambiguously supports the reinstatement of species' seems to us at least highly questionable; in none of the studies they cited in their paper [3][4][5][6][7][8], with the exception of one study [9] done in collaboration with the same authors, is the status of subspecies questioned.…”
mentioning
confidence: 91%
“…Bryant et al recently reported in a study using whole-genome sequencing of isolates from a global collection of clinical isolates that the majority of M. abscessus isolates were dominant circulating clones acquired by transmission between individuals either by fomites or by infectious aerosols and that these clones are associated with worse clinical outcomes and have increased virulence in mouse models thus presenting a serious emerging clinical concern. 69 Identification of NTM is challenging and infection may also easily be missed as organisms are easily overgrown with other bacteria and fungi, and B. cepacia agars have previously been recommended to help with identification. Preece et al have recently reported on their development of a novel agar (RGM medium) that will greatly reduce overgrowth problems and improve the sensitivity of NTM identification.…”
Section: Claire E Wainwrightmentioning
confidence: 99%
“…Importantly, pulmonary infection with M. abscessus complex in people with CF has been associated with accelerated decline in lung function and is of particular clinical concern [4,[8][9][10]. There is also emerging evidence to suggest transmission of M. abscessus complex between individuals with CF [11,12]. NTM PD is challenging to treat requiring multiple antibiotic regimes for a prolonged period of at least 12 months [13,14].…”
Section: Introductionmentioning
confidence: 99%